UPAYA PENINGKATAN PRODUKTIVITAS TANAMAN PADI (Oriza sativa L.) VARIETAS INPARI 32 DENGAN SISTEM JARWO TERHADAP PENGARUH LAMA INDUKSI APLIKASI SIPLO DAN PENAMBAHAN PUPUK ORGANIK - endah nur cayani; Sugiarto Sugiarto; Sunawan Sunawan (AGRONISMA, 2022)
Rice plant (Oriza sativa L.) is a food crop that is needed as an energy source which is generally consumed by the people of Indonesia. The application of SIPLO and the addition of organic fertilizer can make it easier for plants to absorb nutrients in the soil and improve soil fertility. This study aimed to determine the effect of SIPLO induction duration and addition of organic fertilizer on productive tillers, percentage yield, weight of a thousand grains, yield per hectare, and percentage increase in productivity. The factorial RAK (Randomized Block Design) was used in this study. The first factor is the duration of SIPLO induction 20 minutes, 40 minutes, 60 minutes, and 80 minutes. The second factor is the addition of 10 tons/ha and 15 tons/ha organic fertilizers. SIPLO for 60 minutes gave a better yield of 10.22 tons/ha. The addition of 15 tons/ha of fertilizer showed good results of 10.14 tons/ha. If the results of the analysis are real, then it is continued with a regression test to determine the optimum point for SIPLO induction time.Keywords: Rice,jarwo, SIPLO, organic fertilizer